Can image‐enhanced endoscopy improve the diagnosis of Kyoto classification of gastritis in the clinical setting?. Issue 2 (10th October 2019) - Dohi, Osamu; Majima, Atsushi; Naito, Yuji; Yoshida, Takuma; Ishida, Tsugitaka; Azuma, Yuka; Kitae, Hiroaki; Matsumura, Shinya; Mizuno, Naoki; Yoshida, Naohisa; Kamada, Kazuhiro; Itoh, Yoshito
Abstract : Endoscopic diagnosis of Helicobacter pylori ( H. pylori ) infection, the most common cause of gastric cancer, is very important to clarify high‐risk patients of gastric cancer for reducing morbidity and mortality of gastric cancer. Recently, the Kyoto classification of gastritis was developed based on the endoscopic characteristics of H. pylori infection‐associated gastritis for clarifying H. pylori infection status and evaluating risk factors of gastric cancer. Recently, magnifying endoscopy with narrow‐band imaging (NBI) has reported benefits of the accuracy and reproducibility of endoscopic diagnosis for H. pylori‐ related premalignant lesions. In addition to NBI, various types of image‐enhanced endoscopies (IEEs) are available including autofluorescence imaging, blue laser imaging, and linked color imaging. This review focuses on understanding the clinical applications and the corresponding evidences shown to improve the diagnosis of gastritis based on Kyoto classification using currently available advanced technologies of IEEs.